Physiotherapeutic treatment in domestic dogs with lameness of the hind limbs - Pilco P., Marelsy (2017)
The objective of the study was to evaluate the effect of a physiotherapy treatment (massage, thermotherapy, electrotherapy and ultrasound) in the recovery of canine patients with hind limb injuries. The dogs (n=15) were of both sexes, with ages ranging from 5 months to 12 years, who attended the veterinary consultation with claudication of the hind limbs due to hip dysplasia, spondylarthrosis and traumatic neuropathies. The animals were treated for up to a maximum of 12 sessions, where the first six sessions were twice a week and the other six were once a week. Twelve of the 15 patients recovered favorably and three elderly patients did not respond to the treatment. The application of physiotherapy had an 80% effectiveness in canines with hind limbs problems.